Severe human Bocavirus 1 respiratory tract infection in an immunodeficient child with fatal outcome - Tabatabai, Julia; Fakhiri, Julia; Meyburg, Jochen; Linse, Kai-Philipp; Grimm, Dirk; Schnitzler, Paul (The pediatric infectious disease journal, 2019)
We report a case of lower respiratory tract infection with human bocavirus 1 (HboV1) in an immunodeficient 6-month-old boy leading to respiratory failure with fatal outcome. Polymerase chain reaction of serum/tracheal secretions revealed exceptionally high HboV1-DNA levels and immunoassays showed seroconversion indicating an acute primary HboV1 infection. All assays for other pathogens were negative, strongly suggesting that HboV1 was the causative agent in this case.
Gesehen am 09.10.2019